Pengembangan Media Big Book terhadap Pengetahuan Bencana Banjir pada Anak Usia 5-6 Tahun - Ira Agrestin; Eka Cahya Maulidiyah; Faza Karimatul Akhlak' (Universitas Al-Hikmah Indonesia, 2021)
The increasing activity of the population and the need for space is a problem with the development trend in urban areas. Flash floods become the most dominating disaster. Lack of knowledge about the risks of flood disasters makes children the most vulnerable group in society when natural disasters occur. Knowledge of flood disasters needs to be introduced to children from an early age, because disasters have become a routine occurrence in daily life. This development research aims to determine the design of the big book media development and the feasibility of the big book media on knowledge of flood disasters in children aged 5-6 years. This research uses the type of research R & D or (Research and Development) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). This research consists of 3 stages, namely: (1) Analysis, (2) Design, (3) Development. Data collection techniques using questionnaire data. The media big book is A3 size and 18 pages in size, containing material about the causes and consequences of flooding, preparation before, during and after the flood. The big book media display shows the character Kiki with his father and mother during a flood and carrying equipment to face the flood. Feasibility of media products in terms of material and media based on assessment instrument indicators. Based on the analysis of the results of calculations based on the validation test by material experts amounting to 86.1% and media experts by 95.6%, the results are very feasible category. The percentage of results from suggestions and input by 10 PAUD teachers as media users obtained a result of 79.6%, which was categorized as feasible. Thus, the development of the big book media on knowledge of flood disasters in early childhood is deemed appropriate as a learning medium for early childhood.